2021
DOI: 10.1590/1413-81232021264.45952020
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 pandemic in the quality of sleep by Pittsburgh Sleep Quality Index: A systematic review

Abstract: This article aims to evaluate the sleep quality in individuals during the COVID-19 pandemic by Pittsburgh Sleep Quality Index (PSQI). Searches were conducted in the PubMed, Embase, Web of Science, and PEDro databases, on May 22, 2020. In the publications, 208 articles were found and, considering the eligibility criteria, 10 articles were included at the end, showing the effects on sleep quality during the pandemic, in populations hospitalized, quarantined, and in frontline health professionals. The PSQI measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 35 publications
0
29
0
4
Order By: Relevance
“…The PQ is used to detect early onset psychotic symptoms, as psychotic symptoms have been seen manifesting in COVID-19-related conditions ( 14 ). The PSQI is used a self-report sleep measure that is often cited in COVID-19 symptoms ( 15 ). The UCLA Loneliness scale measures reports of loneliness that could result from social isolation faced during quarantine ( 4 ).…”
Section: Methodsmentioning
confidence: 99%
“…The PQ is used to detect early onset psychotic symptoms, as psychotic symptoms have been seen manifesting in COVID-19-related conditions ( 14 ). The PSQI is used a self-report sleep measure that is often cited in COVID-19 symptoms ( 15 ). The UCLA Loneliness scale measures reports of loneliness that could result from social isolation faced during quarantine ( 4 ).…”
Section: Methodsmentioning
confidence: 99%
“…A systematic review of cross-sectional studies reported that sleep quality was poor during the pandemic, not only in HCWs (irrespective of their engagement in the management of COVID-19 patients during the pandemic) but also among nonhospitalized individuals (irrespective of the status of SARS-CoV-2 infection). 18 Interestingly, in most of the studies, poor sleep quality was reported despite spending longer time in bed. 18 This is a situation similar to paradoxic insomnia wherein despite an adequate sleep duration, sleep is still nonrefreshing, perhaps owing to increased cortical activation.…”
Section: Magnitude Of Sleep Disturbances During the Pandemicmentioning
confidence: 99%
“…It is well-known that COVID-19 leads to the commitment of the human health due to injuries in the respiratory tract and central nervous and musculoskeletal systems [3,4], among other specific organs and tissues. Some symptoms observed in the COVID-19 patients are fatigue [97], muscle pain [98], sleep disorders [99,100], and respiratory symptoms [101], these symptoms being also present in individuals with different diseases, such as metabolic syndrome [49,53,73,79], knee osteoarthritis [63,64], and COPD patients [57,80,86,87] which have profited by the management with WBV exercise.…”
Section: Wbve and Mental Conditionsmentioning
confidence: 99%